2020
DOI: 10.1021/acssynbio.0c00040
|View full text |Cite
|
Sign up to set email alerts
|

Transcript Barcoding Illuminates the Expression Level of Synthetic Constructs in E. coli Nissle Residing in the Mammalian Gut

Abstract: The development of robust engineered probiotic therapies demands accurate knowledge of genetic construct expression in the gut. However, the monetary and ethical costs of testing engineered strains in vertebrate hosts are incompatible with current high-throughput design-build-test cycles. To enable parallel measurement of multiple construct designs, we placed unique DNA barcodes in engineered transcripts and measured barcode abundances via sequencing. In standard curve experiments, the barcode sequences exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…To test this hypothesis, we chose three E. coli strains that are useful for different applications. E. coli C600 is a lab strain ( 42 , 43 ), E. coli MG1655 is often used in industrial fermentations ( 44–46 ), and E. coli Nissle 1917 is a probiotic strain ( 5 , 47 , 48 ). We found that phage lysate produced from 10 8 E. coli C600 cells could passage >10 7 variants to E. coli MG1655 and E. coli Nissle 1917 (Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we chose three E. coli strains that are useful for different applications. E. coli C600 is a lab strain ( 42 , 43 ), E. coli MG1655 is often used in industrial fermentations ( 44–46 ), and E. coli Nissle 1917 is a probiotic strain ( 5 , 47 , 48 ). We found that phage lysate produced from 10 8 E. coli C600 cells could passage >10 7 variants to E. coli MG1655 and E. coli Nissle 1917 (Figure 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…With the emerging application of synthetic biology to create programmable bacterial therapeutics, also referred to as AMTs, the need is growing for parts with robust gene expression in vivo. Previous studies 22 have demonstrated that flow-seq is suitable for the high-throughput study of promoters, highlighting a high correlation between GFP protein levels and fluorescence independent of barcoding, as well as a good correlation between the RNA/DNA ratio and GFP fluorescence. Consequently, we leveraged flow-seq to characterize the expression of a 8704 σ 70 promoter library in E. coli Nissle under a range of in vitro and in vivo conditions.…”
Section: ■ Discussionmentioning
confidence: 99%
“…21 Yet, flow-seq has not been widely applied to study the activity of parts-libraries in vivo. 22 T h i s c o n t e n t i s Recent efforts on microbiome expression machinery mainly focused on Bacteroides species due to its abundance in the gut, long term colonization potential, and poorly characterized regulatory elements. 23 A set of inducible promoters and regulatory circuits was developed for Bacteroides thetaiotaomicron and demonstrated to function in vivo based on stoolbased measurements.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel gene circuit topologies continue to increase in complexity as our understanding of the genetic code and its regulation deepens [4,5]. Even our ability to engineer microbes for a variety of settings is expanding to include environments in which they are naturally important, such as soils and gut microbiomes [6,7].…”
mentioning
confidence: 99%